A study of clinical validation of Unani Pharmacopoeial formulation Habb-e-Hilteet in Zu‘f al-Ishtihā’ (anorexia)"at RRIUM, New Delhi: an open prospective clinical trial - Husain, Mohd Talib; Husain, Safder; Sultana, Salma; Khan, Noman; Siddiqui, Zaki Ahmed; Siddiqui, Ziaul Haq (International Journal Of Community Medicine And Public Health, 2025)
Background: Anorexia is a serious condition, especially in older adults, often leading to malnutrition, weight loss, and other severe health problems. Habb-e-Hilteet is a commonly prescribed Unani pharmacopoeial formulation for anorexia. However, no scientific data are available regarding its safety and efficacy. This study assessed the appetite-inducing effect and safety of Habb-e-Hilteet in Zu‘f al-Ishtihā’ (anorexia) patients. Methods: An open prospective clinical trial was conducted in 82 clinically diagnosed anorexia patients of either gender (19-65 yrs old). The study was approved by the institutional ethics committee. Habb-e-Hilteet, one pill (500 mg), was administered orally to patients twice daily for 14 days. The safety of the formulation was assessed using important pathological and biochemical indices and by monitoring adverse events. Efficacy was assessed based on improvement in the Simplified Nutritional Appetite Questionnaire (SNAQ) score. Results: There were 82 participants enrolled in this study. The mean age of the study population was found to be 31.96±11.66years of male, and 31.67±10.81 years of female with a higher rate (69.5%) of occurrence in women. In relation to the Temperament of the Patients, our study found the most effective results in the categories of Damvi (SANGUINE) in 56% of the patients. Our study found a significant correlation (P < 0.000) between the effects of drugs on clinical parameters. Conclusions: The findings of the study suggest that Habb-e-Hilteet may be a safe and effective treatment for anorexia.